Detection of cellular senescence within human invasive breast carcinomas distinguishes different breast tumor subtypes - López-Cotarelo Rodríguez-Noriega, Cristina; Sleeman, Jonathan P.; Thaler, Sonja (OncoTarget, 2016)
Oncotarget | https://doi.org/10.18632/oncotarget.12432 Cristina L. Cotarelo, Arno Schad, Charles James Kirkpatrick, Jonathan P. Sleeman, Erik Springer, Marcus Schmidt, Sonja Thaler
Gesehen am 16.05.2019